Exploring the Capability of Yeasts Isolated from Colombian Fermented Cocoa Beans to Form and Degrade Biogenic Amines in a Lab-Scale Model System for Cocoa Fermentation - Johannes Delgado-Ospina; Laura Acquaticci; Junior Bernardo Molina-Hernandez; Kalliopi Rantsiou; Maria Martuscelli; Astride Franks Kamgang-Nzekoue; Sauro Vittori; Antonello Paparella; Clemencia Chaves-López (Microorganisms, 2020)
Yeast starters for cocoa fermentation are usually tested according to their enzymatic activities in terms of mucilage degradation and flavor improvement, disregarding their influence on the production or elimination of toxic compounds as biogenic amines (BAs), important for human health. In this work, we tested 145 strains belonging to 12 different yeast species and isolated from the Colombian fermented cocoa beans (CB) for their capability of producing BAs in vitro. Sixty-five strains were able to decarboxylate at least one of the amino acids tested. Pichia kudriavzevii ECA33 (Pk) and Saccharomyces cerevisiae 4 (Sc) were selected to evaluate their potential to modulate BAs, organic acids, and volatile organic compounds (VOCs) accumulation during a simulated cocoa fermentation. The growth of Sc or Pk in the presence of CB caused a significant reduction (p < 0.05) of 2-phenylethylamine (84% and 37%) and cadaverine (58% and 51%), and a significant increase of tryptamine and putrescine with a strong influence of temperature in BA formation and degradation. In addition, our findings pointed out that Pk induced a major production of fatty acid- and amino acid-derived VOCs, while Sc induced more VOCs derived from fatty acids metabolism. Our results suggest the importance of considering BA production in the choice of yeast starters for cocoa fermentation.